Factors Influencing Consumers' Decisions To Visit Asia Farm Tourism Objects In Pekanbaru City - Meilany, Merry (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
The aim of this research is to determine and analyze the factors that influence consumer visits to the Asia Farm tourist attraction in Pekanbaru City. The population in this study was all visitors to the Asia Farm tourist attraction in 2023, totaling 60,106 people. Through Slovin formula calculations, a sample size of 100 adult visitors to the Asia Farm tourist attraction was obtained. Data analysis uses multiple linear regression analysis. From the results of filling out the questionnaire by the respondents of this research who are consumers of the Asia Farm tourist attraction in Pekanbaru City, it was concluded that consumers strongly agree, which means that consumers agree to visit the Asia Farm tourist attraction in Pekanbaru City because there are many types of games and games. tourist attraction in it. Based on the results of the hypothesis test carried out, it is known that the three research variables are promotion factors, satisfaction factors and service factors, where the most dominant variable influencing consumer decisions is service (X2). This is proven by the tcount value being smaller than ttable (5,277 > 1.984) and a significance level of 0.05 > 0.000. Thus, it can be concluded that the service factor variable (X2) has a positive and significant effect on consumer decision variables when visiting the Asia Farm tourist attraction in Pekanbaru City